APPLICATION OF NEW METHOD IN ANALYZING AND OVERCOMING LANDSLIDE PROBLEMS USING THE CRACKED SOIL THEORY APPROACH - S.R.B. Prasetyo; Basith Al Hanif; Bagas R. Subchan (University Muhammadiyah Jakarta, 2025)
Landslides often occur unexpectedly, even on slopes previously considered stable according to standard methods, but in reality, the slopes fail. This study presents a method for landslide analysis and mitigation using the concept of cracked soil that considers hidden subsurface cracks as the main triggering mechanism under heavy rainfall conditions. A case study was conducted at the 150 kV SUTT tower site in Segoromadu-Petrokimia, Gresik, Indonesia, where slope failure was observed near critical infrastructure. Comprehensive field investigations, including Standard Penetration Tests (SPT), geoelectric surveys, and laboratory testing have revealed a predominantly stiff clayey silt soil profile with potential cracks between 4–7 meters deep. Slope stability was analyzed using the Limit Equilibrium Method (LEM) under critically saturated and undrained conditions and modeling a weak layer indicated as a cracked layer. The layer was obtained from the interpretation of geoelectrical testing results in the field. The results confirmed that the existing safety factor was below the recommended threshold, especially when considering the tower load. To restore stability, a reinforcement design using mini-piles combined with concrete overlays and sheet piles was proposed. Post-reinforcement analysis showed an overall stability factor exceeding 1.5, validating the design's effectiveness. This study highlights the importance of accounting for subsurface cracks in analyzing slope failure mechanisms to provide mitigation solutions best suited to field conditions.Keywords: Landslide, Cracked Soil Theory, Slope Stability, LEM Analysis